Efforts to increase the added value of belimbing wuluh in Triwungan Village, Kotaanyar District, Probolinggo Regency - Fithri Mufriantie; Jabal Tarik Ibrahim (Journal of Community Service and Empowerment, 2025)
Belimbing wuluh (Averrhoa bilimbi L.) is a fruit plant with multiple uses as a food ingredient, traditional medicine, and raw material for processed food products. Despite its abundance in Triwungan Village, Kotaanyar District, Probolinggo Regency, its economic potential remains underutilized due to the lack of knowledge and skills in value-added processing. This community service project aimed to empower local Family Welfare Movement (Pemberdayaan dan Kesejahteraan Keluarga/PKK) women’s groups through training in processing belimbing wuluh into candied fruit and syrup. The program employed socialization, hands-on workshops, application of simple technology, and evaluation. Results showed that participants successfully produced processed products, gained practical skills, and demonstrated high enthusiasm, with 85% expressing motivation to develop independent micro-enterprises. The activity highlights the importance of community-based training to foster women’s empowerment, resource utilization, and rural entrepreneurship.